2016
DOI: 10.3109/01443615.2016.1154511
|View full text |Cite
|
Sign up to set email alerts
|

The effect of luteal-phase support with vaginal progesterone on pregnancy rates in gonadotropin and clomiphene citrate/intra-uterine insemination cycles in unexplained infertility: A prospective randomised study

Abstract: The purpose of this study is to analyse the effect of luteal-phase support on pregnancy rates in gonadotropin + intra-uterine insemination (Gn/IUI) and clomiphene citrate (CC) +IUI (CC/IUI) cycles in patients with unexplained infertility. Equal numbers of patients were recruited in two treatment arms (CC/IUI and Gn/IUI) (n = 100, n = 100, respectively). In each group, 50 patients received vaginal progesterone for 14 days (Crinone 8% vaginal gel, 90 mg per day) for luteal-phase support from the day after IUI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A total of 31 abstracts were identified, and six full-text articles were reviewed, all of which met full inclusion criteria (17)(18)(19)(20)(21)(22). By combining these six trials with the five studies previously identified in our 2013 meta-analysis ( 13), this updated meta-analysis of 11 RCTs comprised 2,842 patients and 4,065 OI-IUI cycles (17-27) (Supplemental Fig.…”
Section: Studies Included For Systematic Review and Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 31 abstracts were identified, and six full-text articles were reviewed, all of which met full inclusion criteria (17)(18)(19)(20)(21)(22). By combining these six trials with the five studies previously identified in our 2013 meta-analysis ( 13), this updated meta-analysis of 11 RCTs comprised 2,842 patients and 4,065 OI-IUI cycles (17-27) (Supplemental Fig.…”
Section: Studies Included For Systematic Review and Meta-analysismentioning
confidence: 99%
“…Four of these studies specified the use of recombinant FSH for ovulation induction (20,22,23,25), and one study did not list a specific medication beyond describing the use of urinary or recombinant gonadotropins (19). One study described two treatment arms, one of which consisted of patients who received only recombinant FSH and a second arm that included patients who underwent stimulation with CC (21). One trial used either hMG alone or CC plus 2 days of hMG (17).…”
Section: Studies Included For Systematic Review and Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations